Pendidikan Seksual Dalam Pembelajaran Pendidikan Agama Islam - Qodir, Haris Abdul (IJIT: Indonesian Journal of Islamic Teaching, 2024)
Risky sexual behaviours in Indonesia is gradually increasing. In a country where society is based on the values of belief in God, this phenomenon represents an imbalance between morality and reality. Therefore, education is very important to internalise values so that students maintain their sexuality and only express it in ways permitted by religion. State High School (SMAN) 2 of Jember and Al-Furqan High School (SMA) of Jember are chosen as research locations to present educational institutions, especially in Jember Regency, which implement sexual education in Islamic Religious Education (PAI) learning. This research focuses on: 1) PAI learning about manners of associating with the opposite sex at SMAN 2 Jember and SMA Al-Furqan Jember, 2) PAI learning about sexual deviances at SMAN 2 Jember and SMA Al-Furqan Jember. Thus, this research is aimed at: 1) Analysing PAI learning about manners of associating with the opposite sex at SMAN 2 Jember and SMA Al-Furqan Jember, 2) Analysing PAI learning about sexual deviances at SMAN 2 Jember and SMA Al-Furqan Jember. This research uses a qualitative approach with the type of collective case study. Research subjects are determined purposively while data collection is carried out through interviews, observations, and document studies. The data is analysed using the interactive data analysis model by Miles, et al and the explanation building model by Robert K. Yin. The validity of the data is checked through persistent observation, triangulation, use of reference materials, and peer debriefing. The findings of this research show: 1) PAI learning about manners of associating with the opposite sex at SMAN 2 Jember and SMA Al-Furqan Jember is integrated into the learning chapter on avoiding adultery and promiscuity. The success of this learning cannot be determined because there is no comprehensive evaluation to measure the achievement of learning objectives. SMAN 2 Jember compromises the concept of Islamic Religious Education with the cultural reality of public school which results in a synthesis, namely the partial implementations of the Islamic Religious Education concept on manners of associating with the opposite sex, while SMA Al-Furqan Jember strictly enforces the Islamic Religious Education concept on manners of associating with the opposite sex as an absolute value through repressive measures. 2) PAI learning about sexual deviance at SMAN 2 Jember and SMA Al-Furqan Jember focuses on discussing adultery which is also integrated into the learning chapter on avoiding adultery and promiscuity. This learning is supported by the rule prohibiting students from committing immoral acts at SMAN 2 Jember, while at SMA Al-Furqan Jember the rule is anticipated earlier for actions that are considered "near to adultery".